PERANAN DPRD MEWUJUDKAN PENDIDIKAN BERBASIS BUDAYA DI KABUPATEN KUTAI KARTANEGARA - Supriyadi Supriyadi (Fakultas Agama Islam Universitas Kutai Kartanegara, 2018)
Kutai Kartanegara regency as one of the areas rich in customs, arts and traditional culture, is expected to make the cultural base as education. The Regional People's Legislative Assembly (DPRD) of Kutai Kartanegara Regency is expected to be able to bridge the issue, especially with the regional policy through Local Regulation (Perda) No. 15/2010 on Education Implementation System. This paper seeks to empower the cultural potential of the district of Kutai Kartanegara through education policy that sustains all subcultures in Kutai Kartanegara Regency, through the role of DPRD of Kutai Kartanegara Regency.